Indigenous Community Mobilization for Violence Prevention - Pepler, Debra; Ricard, Dawn-Lee; Cardinal, Shelley (The International Indigenous Policy Journal, 2026)
For over 25 years, the Canadian Red Cross (CRC) has been invited into Indigenous communities across Canada to support them in mobilizing to prevent violence and create safe environments to promote wellness for children and youth. We collaborated with four Indigenous communities to understand community mobilization processes. Community-based researchers ensured that the research was culturally appropriate. Conversations with community members who participated in CRC’s Ten Steps workshop were transcribed and qualitatively coded. We are reporting on the 15 themes that were common across the four communities. Ten common themes emerged related to how the workshop supported communities to mobilize and work cohesively to prevent violence. Five additional themes arose from community members’ suggestions for future programming and are described following the seven questions. Communities recognized the value of the CRC programming to create safe environments for children and youth.